Mechanics of Soft Materials - Volokh, Konstantin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a concise introduction to soft matter modelling, together with an up-to-date review of the continuum mechanical description of soft and biological materials, from the basics to the latest scientific materials. It also includes multi-physics descriptions, such as chemo-, thermo-, and electro-mechanical coupling. The new edition includes a new chapter on fractures as well as numerous corrections, clarifications and new solutions. Based on a graduate course taught for the past few years at Technion, it presents original explanations for a number of standard materials, and features detailed examples to complement all topics discussed.
Tensors -- Kinematics -- Balance laws -- Isotropic elasticity -- Anisotropic elasticity -- Viscoelasticity -- Chemo-mechanical coupling -- Electro-mechanical coupling.
Keywords: Mechanics, Applied; Solids; Soft condensed matter; Biomaterials; Solid Mechanics; Soft and Granular Matter; Biomaterials